2010
DOI: 10.1007/s00299-010-0856-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of two different types of heat stress on chloroplast movement and fluorescence signal of tobacco leaves

Abstract: Although the chloroplast movement can be strongly affected by ambient temperature, the information about chloroplast movement especially related to high temperatures is scarce. For detailed investigation of the effects of heat stress (HS) on tobacco leaves (Nicotiana tabacum L. cv. Samsun), we used two different HS treatments in dark with wide range of elevated temperatures (25-45 degrees C). The leaf segments were either linearly heated in water bath at heating rate of 2 degrees C min(-1) from room temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Some studies have shown that during desiccation, the nonchloroplast water is lost faster than so called chloroplast water (McCain et al 1988;Carter and McCain 1993;Ning et al 1994), which means that the water surrounding thylakoid membranes and particularly PSII complex remains unchanged longer than the cytoplasmic medium and cytoplasm in epidermal cells. It is interesting to note that even the high temperature stress, which is relatively homogeneously distributed in leaf tissue, is detected sooner by chloroplast movement than by Chl fluorescence (the O-J-I-P curve; Frolec et al 2010). It is possible that the changes in light-induced chloroplast movement represent an early signal of a general stress situation.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Some studies have shown that during desiccation, the nonchloroplast water is lost faster than so called chloroplast water (McCain et al 1988;Carter and McCain 1993;Ning et al 1994), which means that the water surrounding thylakoid membranes and particularly PSII complex remains unchanged longer than the cytoplasmic medium and cytoplasm in epidermal cells. It is interesting to note that even the high temperature stress, which is relatively homogeneously distributed in leaf tissue, is detected sooner by chloroplast movement than by Chl fluorescence (the O-J-I-P curve; Frolec et al 2010). It is possible that the changes in light-induced chloroplast movement represent an early signal of a general stress situation.…”
Section: Resultsmentioning
confidence: 98%
“…The T C dependence on time of blue light exposure, the T C (t) curve, reflecting the chloroplast avoidance movement, was characterized by a sigmoidal increasing shape (see Nauš et al 2008, Frolec et al 2010. We used an illumination time of 25 min, which was time necessary to reach the beginning of the T C plateau in control leaves (Fig.…”
Section: Light-induced Chloroplast Avoidance Movementmentioning
confidence: 99%
See 3 more Smart Citations